Practical activities of social work students Trade Union University - Phạm Thị Hồng Bích; Trương Thị Ly (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
Social work practice is an important component of social work bachelor’s degree programs. In order to fully equip students with knowledge and skills, beyond theoretical learning in classrooms, social work students need direct practical experience at facilities. Through practical experience, students can bridge the gap between theory and reality, gain foundational knowledge, general practical skills, and opportunities to experience values, thus forming their professional skills. In this article, the author clarifies the practical model and the limitations encountered in the practical activities of social work students at the Faculty of Social Work, Trade Union University. The author proposes solutions to enhance the effectiveness and quality of practical training for students in the Faculty of Social Work, Trade Union University.